Saying no to the glow: When consumers avoid arrogant brands. Issue 2 (21st May 2015) - Munichor, Nira; Steinhart, Yael
Abstract: Arrogant brands have a multifaceted influence on consumers: Although consumers appreciate arrogant brands as reflecting high status and quality, arrogance can also make consumers feel inferior. Consumers whose self is a priori threatened may consequently "say no to the glow" and avoid arrogant brands. Results from six experiments using fictitious or actual arrogant brands show that when consumers experience prior self‐threat, they may avoid brands that convey arrogance in favor of a competing, less‐arrogant alternative. Such avoidance helps self‐threatened consumers restore their self‐perceptions and feel better about themselves.